Hakikat Tuhan: Kajian Pemikiran Islam dalam Falsafah Jawa - Syarifah Wardah el Firdausy (SHAHIH: Journal of Islamicate Multidisciplinary, 2017)
Islamic thought in the Javanese philosophy of the concept of God begins with the existence of three continuities between (1) the background of Islamization in Indonesia, through cultural approaches, (2) philosophical phrases in the Javanese philosophy as a part of the characteristic Javanese literary works that are educational (didactic) and sublime (piwulang), and (3) the similarity between the concept of tri hita wacana means harmonious relationship of man with God (habluminallah) in Islamic teachings related to the concept of insan kamil. This study uses qualitative methods based on literature study data and descriptive analysis as a whole (integral). The results obtained from this study is the similarity of thinking between the philosophical expressions of Java in the Javanese philosophy with Islamic thought in the verses of the Qur'an as part of the teachings of Islam in understanding the three concepts of the nature of God that is (1) the concept of tan kena kinaya gapa means that God cannot be imagined circumstances and forms, but the absolute power, (2) the concept of Gusti Allah orah sare means God is not sleeping and always awake in every period; Understanding of the concept raises an attitude of being cautious in acting, acting, and fully aware of God's supervision, and (3) the concept of sangkan paran which has an understanding that the beginning of the creation of man and the universe comes from God (sangkan) and the end of creation Man and the universe will return to God (paran).